Insurgent - Roth, Veronica (New York Katherine Tegen Books, 2015)
"As war surges in the dystopian society around her, sixteen-year-old Divergent Tris Prior must continue trying to save those she loves--and herself--while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love"--Provided by publisher for hardcover edition.
Bonus material. Insurgent alternative beginning -- Evelyn's speech to the factionless -- The reality of grief -- Veronica Roth's faction playlists -- Insurgent discussion questions -- An excerpt form Allegiant.
Sequel to: Divergent.
Sequel: Allegiant.
Keywords: Courage -- Juvenile fiction; Dystopias -- Juvenile fiction; Grief -- Juvenile fiction; Politics, Practical -- Juvenile fiction; Loyalty -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Families -- Juvenile fiction; Social classes -- Juvenile fiction; Identity -- Fiction; Families -- Fiction; Courage -- Fiction; Social classes -- Fiction